Etnomatematika pada Permainan Tradisional Porok di Desa Penaga - Husna, Nindita Asma Ul; Febrian, Febrian; Risky, Muhamad; Arifin, Yesica Salshabila; Hamudin, Irna Andriani; Sarah, Sarah; Anderi, Anderi; Hakim, Usnul; Wardina, Fildza (Jurnal Gantang, 2023)
Ethnomathematics is a science that studies the existence of mathematical concepts in social culture. One of the cultures in Indonesia is traditional games, which are a reflection of local wisdom. Traditional games can be linked to mathematics learning through an ethnomathematics approach. One example is the game of porok. The Porok game is among the most popular traditional games in Penaga Village, Bintan Bay and the Riau Islands. This game can potentially be explored regarding its use in mathematics learning. Thus, this research aims to dig deeper into the mathematical concepts and activities of the porok game as a form of ethnomathematics. This research uses a qualitative approach with an ethnographic design. The data source for this research is the head of the Dang Merdu studio in Penaga Village, Bintan Regency. Data collection was carried out through observation, interviews and documentation. The data analysis technique is carried out through 4 stages of analysis: domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The research found basic activities and mathematical concepts in this game. The mathematical activities obtained are counting, measuring, explaining, playing and planning. Apart from that, this game has mathematical concepts, namely, value comparison, addition, geometric figures and probability, arithmetic sequences and series, probability and rotation.